Usages du « genre » à l’Université : sur l’institutionnalisation des études féministes en Roumanie - Ioana Cîrstocea (Genre & Histoire)
Providing a brief overview of the feminist studies’ institutionalization in 1990s Romania, the paper analyses the context of this process, closely connected to some opportunities coming from the NGOs’ action and generally from the transnational programs promoting women’s rights within the democratization of the ex-communist countries. Various uses of gender are then reviewed. First, we insist on the uses of the notion itself, who entered the contemporary Romanian public discourse in order to refer to women and to the equality between men and women. Second, we look at the strictly social uses of the gender themes and we show how they are appropriated by young members of the academic community and mobilized as a cultural ressource in the professional struggles that characterize a restructurating social sciences field.